Microstructure and Corrosion Behavior of the Friction Stir Welded Joints Made from Ultrafine Grained Aluminum1 . Issue 7 (18th April 2017) - Lipińska, Marta; Ura‐Bińczyk, Ewa; Olejnik, Lech; Rosochowski, Andrzej; Lewandowska, Małgorzata
Abstract : Joints made from ultrafine grained aluminium alloy 1050 are investigated in order to examine the corrosion behavior and microstructural changes between base materials and stir zones. Samples in the initial state, after four and eight passes of Incremental ECAP (I‐ECAP) process were joined with similar plates using Friction Stir Welding. Initially refined microstructure after I‐ECAP transformed to homogenous few micron sized grains structure in stir zones. AlFeSi particles present in the microstructure became fragmented during plastic deformation and welding process. The observed minor differences in corrosion resistance include slightly higher values of corrosion potentials but more complex pits' morphology for I‐ECAP processed samples comparing to the stir zones. Abstract : The changes in the microstructure and corrosion resistance between base materials (BM) and stir zones (SZ) are investigated. The number refers to the number of I‐ECAP passes of base material. After the corrosion tests, the surface of the samples was examined using SEM. With increasing number of I‐ECAP passes, the pits pose more developed structure with linked cavities. For SZ samples, which exhibit higher grain size, the number of pits is reduced. Pits are also less developed but deeper. The number of pits and surface covered by them is connected with size of AlFeSi particles.